Potent inhibition of miR-27a by neomycin-bisbenzimidazole conjugates - Nahar, Smita; Ranjan, Nihar; Ray, Arjun; Arya, Dev P.; Maiti, Souvik (Chemical Science, 2015)
miRNAs are important components of regulatory networks that control gene expression and have implications in various diseases including cancer. Targeting oncogenic miRNAs with small molecules is currently being explored to develop cancer therapeutics. Here, we report the development of dual binding neomycin-bisbenzimidazole conjugates that target oncogenic miR-27a with high affinity (K-a = 1.2 to 7.4 x 10(8) M-1). These conjugates bring significant reduction (similar to 65% at 5 mu M) in mature miRNA levels and penetrate easily in the cells where they localise both in the cytoplasm and the nucleus. Cell cycle analysis showed significant increase in the G0/G1 phase (similar to 15%) and decrease in the S phase (similar to 7%) upon treatment with neomycin-bisbenzimidazole conjugates, suggesting inhibition of cell proliferation. Using the conjugation approach, we show that moderately binding ligands can be covalently combined into high affinity binders. This study also highlights the role of linker optimization in designing high affinity ligands for miR-27a targeting.

Selective inhibition of miR-21 by phage display screened peptide - Bose, Debojit; Nahar, Smita; Rai, Manish Kumar; Ray, Arjun; Chakraborty, Kausik; Maiti, Souvik (Nucleic Acids Research, 2015)
miRNAs are nodal regulators of gene expression and deregulation of miRNAs is causally associated with different diseases, including cancer. Modulation of miRNA expression is thus of therapeutic importance. Small molecules are currently being explored for their potential to downregulate miRNAs. Peptides have shown to have better potency and selectivity toward their targets but their potential in targeting and modulating miRNAs remain unexplored. Herein, using phage display we found a very selective peptide against pre-miR-21. Interestingly, the peptide has the potential to downregulate miR-21, by binding to pre-miR-21 and hindering Dicer processing. It is selective towards miR-21 inside the cell. By antagonising miR-21 function, the peptide is able to increase the expression of its target proteins and thereby increase apoptosis and suppress cell proliferation, invasion and migration. This peptide can further be explored for its anti-cancer activity in vivo and may be even extended to clinical studies.

Francisella novicida Cas9 interrogates genomic DNA with very high specificity and can be used for mammalian genome editing - Acharya, Sundaram; Mishra, Arpit; Paul, Deepanjan; Ansari, Asgar Hussain; Azhar, Mohd; Kumar, Manoj; Rauthan, Riya; Sharma, Namrata; Aich, Meghali; Sinha, Dipanjali; Sharma, Saumya; Jain, Shivani; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Genome editing using the CRISPR/Cas9 system has been used to make precise heritable changes in the DNA of organisms. Although the widely used Streptococcus pyogenes Cas9 (SpCas9) and its engineered variants have been efficiently harnessed for numerous gene-editing applications across different platforms, concerns remain regarding their putative off-targeting at multiple loci across the genome. Here we report that Francisella novicida Cas9 (FnCas9) shows a very high specificity of binding to its intended targets and negligible binding to off-target loci. The specificity is determined by its minimal binding affinity with DNA when mismatches to the target single-guide RNA (sgRNA) are present in the sgRNA:DNA heteroduplex. FnCas9 produces staggered cleavage, higher homology-directed repair rates, and very low nonspecific genome editing compared to SpCas9. We demonstrate FnCas9-mediated correction of the sickle cell mutation in patient-derived induced pluripotent stem cells and propose that it can be used for precise therapeutic genome editing for a wide variety of genetic disorders.
Keywords: CRISPR Cas9; gene therapy; Genome editing; iPSCs; sickle cell anemia

Small molecule quercetin binds MALAT1 triplex and modulates its cellular function - Rakheja, Isha; Ansari, Asgar Hussain; Ray, Arjun; Joshi, Dheeraj Chandra; Maiti, Souvi (Molecular Therapy-Nucleic Acids, 2022)
The triple-helix structure at the 30 end of metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), a long non -cod-ing RNA, has been considered to be a target for modulating the oncogenic functions of MALAT1. This study examines the binding of quercetin-a known triplex binding molecule-to the MALAT1 triplex. By employing UV-visible spectroscopy, circular dichroism spectroscopy, and isothermal titration calo-rimetry, we observed that quercetin binds to the MALAT1 triplex with a stoichiometry of 1:1 and Kd of 495 +/- 61 nM, along with a negative change in free energy, indicating a spontaneous interaction. Employing real-time PCR measurements, we observed around 50% downregulation of MALAT1 transcript levels in MCF7 cells, and fluorescence in situ hybridization (FISH) experiments showed concomitantly reduced levels of MALAT1 in nuclear speckles. This interaction is likely a result of a direct interaction between the molecule and the RNA, as indicated by a transcription-stop experiment. Further, tran-scriptome-wide analysis of alternative splicing changes induced by quercetin revealed modulation of MALAT1 downstream genes. Collectively, our study shows that quercetin strongly binds to the MALAT1 triplex and modulates its functions. It can thus be used as a scaffold for further development of ther-apeutics or as a chemical tool to understand MALAT1 func-tions.

Molecular modeling of non-canonical intramolecular RNA triple helix structures predicted from TRIPinRNA and their in vitro biophysical structure validation - Rakheja, Isha; Panda, Gayatri; Maiti, Souvik; Ray, Arjun (Journal of Physical Chemistry B, 2025)
RNA triple helices have traditionally been characterized by pyrimidine-type UA-U or CG-C triplets, with other base triplets considered to be destabilizing. However, the presence of non-canonical triplets in riboswitches and self-splicing introns suggests that triplexes containing longer stretches of such triplets may exist in the human genome too. Using molecular modeling, we investigated a chimeric triple helix derived from the FLRT2-AS1 lncRNA, confirming its stability over a 500 ns simulation. Biophysical analyses further support the formation of this triplex in vitro. Although these non-canonical structures exhibit less thermal stability compared to traditional UA-U triplets found in lncRNAs like metastasis associated lung adenocarcinoma transcript 1 and NEAT1, they may serve distinct biological functions, suggesting a dynamic and more temporal role in cellular processes. The triplex selected for this study is found in a human long non-coding RNA gene, paving the way for investigating the intriguing roles of these triple helices in cell biology.